The Journey of Plastics: Historical Development, Environmental Challenges, and the Emergence of Bioplastics for Single-Use Products - Jade Stanley; David Culliton; Antonio-Jonay Jovani-Sancho; Adriana Cunha Neves (Eng)
This paper explores the historical development of conventional plastics, tracing their evolution from early forms to their pervasive use in modern society. Its observations include the rise of mass plastic production during World War II and the post-war development, showcasing plastics’ economic and societal impact. The environmental repercussions of plastic pollution have led to increased global awareness and calls for sustainable alternatives. The emergence of bioplastics is investigated, including their classification, properties, applications, and challenges in scaling. This paper emphasises the urgency of adopting bioplastics for a sustainable future and discusses efforts towards homogenisation and standardisation across global markets.